Characterization and reliability of Ag nanoparticle sintered joint for power electronics modules - Wang, Yun (2016)
Nowadays, numerous power electronics application requires operation at high temperatures. In order to address increasing change of reliability problems in power die attachments for high temperature and high reliability applications, sintering Ag nanoparticles has been used as bonding material for this work. Firstly, quantitative microstructure characterization of as-sintered Ag joints has been carried out. The resulting normalized thickness, pore size and porosity decreased, and grain size increased with increasing the sintering time. A time dependence of the form t1/n with n close to 2 or 3 can be further derived for the kinetics of the thinning, densification and grain growth within the sintered Ag joints. From the results can be seen, sintering kinetics is still in the intermediate stage, the densification had not been completed, and Ag grain would continue growing afterwards, which could further explain degradation behaviours of sintered joints during isothermal ageing tests and thermal cycling tests. Secondly, sintered Ag joints with four kinds of substrate metallization have been subjected to isothermal ageing tests at temperatures of 150°C, 200°C and 250°C for up to 32 days. The different microstructure patterns of sintered joints with four substrate finishes during isothermal ageing tests have been presented and compared, which could use the results to explain part of the degradation behaviours of the sintered Ag joints during thermal cycling tests and guide selection of suitable substrate finish for the die attachments in high temperature power electronic system. Furthermore, thermal cycling tests have been carried out to investigate the reliability of two sizes of sintered Ag joints and solder joints during temperature cycling between -55°C to 125°C and -55°C to 150°C. Microstructure evolution of sintered Ag joints was investigated by non-destructive and destructive characterization methods, which revealed the factors which could effect on the degradation during thermal cycling tests. With microstructure features of sintered joints observed from X-ray tomography and SAM, because a specific specimen can be evaluated over its lifetime, a true image of microstructure evolution of damage during operation can be obtained, and crack and degradation can be observed three-dimensionally.